2008
DOI: 10.1038/cgt.2008.25
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral-mediated Rybp expression promotes tumor cell-specific apoptosis

Abstract: Previous work demonstrated that exogenous expression of Rybp (Ring 1 YY1-binding protein or DEDAF) kills tumor but not nontransformed cells. This tumor-preferential killing activity could be exploited in a gene therapy approach to treat cancer. To test the potential of viral-mediated delivery of Rybp as an anticancer treatment, we generated an adenovirus expressing Rybp (Ad-Rybp). Infection with Ad-Rybp inhibits the proliferation of a range of tumor cell lines, but has no effect on normal cell types. This inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 28 publications
3
28
0
Order By: Relevance
“…RYBP (RING1 and YY1 binding protein, also known as DEDAF) functions as a repressor of E4TF1 and induces apoptosis in tumour cells (Danen-van Oorschot et al 2004). The preferential tumour-killing activity of RYBP has made it a promising target for cancer therapy (Novak & Phillips 2008).…”
Section: Discussionmentioning
confidence: 99%
“…RYBP (RING1 and YY1 binding protein, also known as DEDAF) functions as a repressor of E4TF1 and induces apoptosis in tumour cells (Danen-van Oorschot et al 2004). The preferential tumour-killing activity of RYBP has made it a promising target for cancer therapy (Novak & Phillips 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, high levels of dRYBP expression induce apoptosis in all the imaginal discs studied (Figure 1). In transfection experiments, murine and human RYBP/DEDAF proteins have been shown to have the ability to specifically kill mammalian tumor cells while leaving normal cells unaffected [19,20]. We have shown that the induction of apoptosis in Drosophila does not require the apoptotic cell to be in the transformed state, indicating that this may be a useful system to study the mechanisms controlling the tumor-specific cell killing.…”
Section: High Levels Of Exogenous Drybp Induce Apoptosismentioning
confidence: 92%
“…In mammals, high levels of the RYBP protein have been found to have tumor-specific killing activity, a characteristic that could potentially be exploited to develop anti-cancer treatments [19]. Furthermore, the RYBP protein has been found to interact with Apoptin, a protein known to be active in killing tumor cells [20].…”
Section: Introductionmentioning
confidence: 99%
“…The functional importance of deleted RYBP in ileal carcinoids still remains to be determined. However, targeting of cancer cells by adenoviral-mediated RYBP expression induces tumor cell-specific apoptosis [77]. Collectively, these data suggest that targeting of RYBP may be a treatment option in a proportion of ileal carcinoids.…”
Section: Genomic Profiling Of Ileal Carcinoidsmentioning
confidence: 97%